Fused Deposition Modeling of Single-Use Plastic Alloy - Wang Liao; Jie Wang; Manping Pan (Advances in Polymer Technology)
Packaging plastics are called ‘single-use plastics’ because of short lifetime. Among which, the three plastics of polyethylene (PE), polypropylene (PP), and polyethylene terephthalate (PET) take more than 70%. Due to incompatibility, few research has been done on the alloy of the three plastics. The aim of this study is to investigate the possibility of single-use plastic alloy (SUPA) of ternary PE, PP, and PET as the 3D printing material. Tensile and bending tests are carried out to investigate the mechanical properties, photographs of scanning electron microscope (SEM) are taken for morphology analysis, and differential scanning calorimetry (DSC) are used to study the crystallization behavior of the alloys. The results show that there is an optimal ratio for all the components to obtain the best mechanical performances, i.e., the ratio of PP/PE=40/60 with 20 wt% PET, 2 wt% maleic anhydride grafted polypropylene (PP-g-MAH) and 2 wt% organic modified montmorillonite (OMMT). This SUPA has a tensile strength of 14.48 MPa, a tensile modulus of 586.42 MPa, a flexural strength of 15.85 MPa, and a flexural modulus of 544.67 MPa. Due to the function of compatibilizer and nanoclay (NC) will be affected by redundancy, the potential primary fibrosis while collecting the feeding filaments and the secondary fibrosis at the nozzle of 3D printing might be responsible for the variation of the mechanical performances.